Reconstruction of dissolved oxygen in the Indian Ocean from 1980 to 2019 based on machine learning techniques - Huang, Sheng; Shao, Jian; Chen, Yijun; Qi, Jin; Wu, Sensen; Zhang, Feng; He, Xianqiang; Du, Zhenhong (Frontiers in Marine Science, 2023)
Oceanic dissolved oxygen (DO) decline in the Indian Ocean has profound implications for Earth's climate and human habitation in Eurasia and Africa. Due to sparse observations, there is little research on DO variations, regional comparisons and its relationship with marine environmental changes in the entire Indian Ocean. In this study, we applied machine learning methods to reconstruct the four-dimensional DO dataset in the Indian Ocean from 1980 to 2019 using ocean reanalysis data and spatiotemporal information. Overall, a deoxygenation trend of −141.5 ± 15.1 Tmol dec −1 was estimated over four decades, with a slowdown trend of −68.9 ± 31.3 Tmol dec −1 after 2000. DO decline and oxygen-minimum zones (OMZ) expansion were prominent in the Arabian Sea, Bay of Bengal, and Equatorial Indian Ocean. Through correlation analysis, we found that temperature and salinity changes related to solubility primarily control the oxygen decrease in the deep sea. However, the complicated factors with solubility change, vertical mixing and circulation, govern the oxygen increase in the upper and middle sea. Under global warming and climate change, deteriorations of OMZ expanding and deoxygenation in the Indian Ocean are gradually mitigating. This study enhances our understanding of DO dynamics of the Indian Ocean in response to deoxygenation.